Pengaruh Pendapatan Dan Pengetahuan Tentang Zakat Terhadap Kesadaran Muzakki Dalam Menunaikan Zakat Profesi Di Upz Kecamatan Cipondoh Kota Tangerang - Muizzudin, Muizzudin; Hapstari, Ayu (Zhafir | Journal of Islamic Economics, Finance, and Banking, 2021)
The research is aimed at measuring the impact of earning (X1), knowledge on zakat (X2) on the awareness of the zakat payer in implementing zakat of profession. The method used is quantitative with the use of the questionnaire. The number of the respondents is 55 zakat payers. The technique to take samples is purposive sampling, with the use of regression statistics to accommodate the awareness of zakat as dependent variable (Y), the earning (x1), and the knowledge on zakat (X2). Multiple linear regression is used to test the impact of the two independent variables on the dependent variables partially and wholly by applying the software of SPSS 26. The results show that only the knowledge on zakat partially has a positive impact in paying zakat of profession. The earning (X1) partially doesn’t give the impact on the paying of zakat of profession. However, the two independent variables wholly have the impact on the dependent variable.